Dietary variability and micronutrient status of individuals with Yaws infection in Ghana: A case-control study - Abigail Agbanyo; Michael Ntiamoah Oppong; Ruth Dede Tuwor; Pius Takyi; Felix Wireko; Philemon Boasiako Antwi; Dzifa Kofi Ahiatrogah; Aloysius Dzigbordi Loglo; Bernadette Agbavor; Alex Owusu-Ofori; Richard Odame Phillips; Yaw Ampem Amoako (PLoS ONE, 2025)
Background Yaws is a neglected tropical skin disease mainly affecting children under 15 years. It is targeted for eradication by 2030 through Mass Drug Administration (MDA) of a single oral dose of azithromycin (30 mg/kg), which has achieved about a 95% cure rate. Despite this, the disease persists in endemic countries. Eradication requires addressing contributing factors, including the role of nutrition in yaws; yet this remains underexplored. This study assessed the nutritional status of individuals in yaws-endemic areas using a case-control design. Methods A case-control study was conducted from May to November 2024 in 33 communities across two districts in Ghana. Cases were Dual Path Platform (DPP) positive individuals, matched by age and sex with healthy controls. Data collection included demographic and anthropometric measurements and a Ghana-specific multi-pass 24-hour dietary recall. Results A total of 64 cases and 64 matched controls [median age 11.5 years, Interquartile range (IQR) 9–13.8] were enrolled. Moderate stunting was found in 27% of cases and 22% of controls; severe stunting in 6% and 5%, respectively. Roots and tubers were consumed by all participants, while fruit intake was low (5% overall; 3% in cases, 8% in controls). Controls generally had slightly higher micronutrient intake than cases, except for energy (1754 ± 657 kcal vs. 1726 ± 707.3 kcal), fat (55.15 ± 28.04 g vs. 51.83 ± 27.04 g), and vitamin C (108.7 ± 42.24 mg vs. 107.7 ± 53.18 mg). No statistically significant differences in nutrient adequacy were found between healed and non-healed yaws cases (p > 0.05), though participants with non-healed lesions more often had inadequate intakes of energy (88% vs. 80%), fibre (100% vs. 96%), iron (63% vs. 54%), zinc (75% vs. 71%), and vitamin B12 (63% vs. 55%). Conclusion In these yaws-endemic districts, we observed high levels of undernutrition and micronutrient deficiencies among both cases and controls. Although nutritional status was not independently linked to poorer treatment outcomes, the burden of malnutrition underscores the need for integrated health interventions. Further research is warranted to clarify the relationship between chronic nutritional deficiencies and yaws outcomes.